Study of new age liposomes :|transethosomes - Güler, Canan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Liposomes are vesicles formed by the self-arrangement of amphiphilic molecules into bilayer form, enclosing an aqueous core. The fact that these vesicles resemble the skin structure makes them ideal carriers for active drug or cosmetic ingredients into the skin. In order to effectively deliver ingredients under the skin, deformable vesicles such as ethosomes or transfersomes are designed. A new form of deformable vesicles is the transethosomes. These vesicles can deform when under stress without breaking and release their content once they are under the skin. Transethosomes are vesicles containing edge activators or permeation enhancers and ethanol. In this study, transethosomes containing different edge activators/permeation enhancers were investigated and compared. Ethanol and oleic acid were incorporated within the lipid bilayer as permeation enhancers and polysorbate (Tween®80) was added separately as an edge activator. Effects of different preparation methods were reported in terms of size, size distribution, surface charge and morphology. Also effects of different concentrations of edge activator/permeation enhancer were investigated. Considering their wide biochemical and pharmacological benefits and the fact that transethosomes can better encapsulate lipophilic molecules, two essential oils, geraniol and linalool were encapsulated.
Keywords: Liposomes.